THE RELATIONSHIP BETWEEN NUTRITIONAL INTAKE AND KNOWLEDGE LEVELS ON BLOOD PRESSURE IN ELDERLY OF POSBINDU NUSA INDAH II, TANAH KUSIR, SOUTH JAKARTA - Mitha Monica; Moesijanti Y. E. Soekatri (Politeknik Kesehatan Kemenkes Jakarta II, 2021)
Abstract The elderly might at risk of developing hypertension. Basic Health Research in 2018 showed that prevalence of hypertension was 34.1%, there is a significant increase from 2007 with percentage of 28.8%. The purpose of this study was to determine the relationship between intake of sodium, potassium, calcium, fiber and the knowledge levels on blood pressure. The subjects of this study were the elderly with hypertension who were registered at Posbindu Nusa Indah II. Samples were taken purposively sampling technique and obtained as many as 17 people. Respondent characteristic data were gender, age, history of hypertension, last education. Food intake data obtained from food recall form 2 days not in a row. Statistical analysis using Spearman correlation test. The results showed that there was no significant relationship between intake of sodium, potassium, calcium, fiber, and level of knowledge on blood pressure (p> 0.05). The conclusion is although there is no significant relationship but there is a tendency if higher or lower intake of sodium, potassium, calcium, fiber, and level of knowledge to increase or decrease the blood pressure. The recommendation of this research is the collaboration between Posbindu Nusa Indah II with the Nutrition Department to conduct counseling for hypertension sufferers.